Accreditation recognises excellent people management at PPE. Issue 9 (September 2017) - Unknown
Abstract : Precision Polymer Engineering Ltd (PPE), a manufacturer of high-performance moulded elastomer seals and O-rings, based in Blackburn, UK, has achieved 'Investors In People' accreditation.